Effect of Different Concentrations of Trehalose on Post-Thaw Quality of Surti Buffalo (Bubalus bubalis) Bull Semen - Kumar, Naveen; Gaur, Mitesh; Jhamb, Dinesh; Vyas, Jayesh (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to investigate the effects of supplementation of trehalose as an additive in Tris-Fructose-Egg Yolk-Citrate extender on post-thaw semen quality in 24 ejaculates of six Surti buffalo bulls. Semen extended @ 80 million sperm /ml was divided into four equal parts and served as three treatment group as T1 (50 mM trehalose), T2 (100 mM trehalose) and T3 (150 mM trehalose) and one as control (T0). The percentage of post-thaw sperm progressive motility, sperm viability, HOS responsive sperm were higher, whereas sperm abnormalities were lower in treatment T1, T2 and T3 as compared to control. The treatment T2 (100 mM trehalose) had significantly higher post-thaw progressive motility, sperm viability, HOS response sperm percentage and reduced sperm abnormalities as compared to control and other levels of trehalose. In conclusion, supplementation of trehalose at 100 mM concentration significantly (p
Keywords: Cryopreservation; Extender; Semen; Surti bull; Trehalose